Visualization of sorting algorithms in the virtual reality environment - Mukasheva, Manargul; Kalkabayeva, Zukhra; Pussyrmanov, Nurbek (Frontiers in Education, 2023)
This study examines the use of virtual reality (VR) in programming, specifically in visualization of sorting methods. Addressing students’ needs to better understand and implement sorting methods, “VR sorting” application was developed to visualize the bubble sorting and selection sorting abstract methods in the VR environment. The effects of visualization were evaluated drawing on an extended taxonomy, specifically developed by the authors of this study. The results indicate that VR might significantly enhance students’ understanding of sorting tasks, further allowing them to employ these skills in practice. Specifically, 76.9% of students, who studied sorting methods in virtual environment drawing on "VR sorting" application, demonstrated higher outcomes in implementing sorting tasks. VR visualization of sorting methods, differs from existing ways of visualizing learning in the context of constructivism. Since VR allows the student to construct the algorithm himself directly interacting machine memory in the form of cells where the data is stored and managing the progress of sorting. These results shed some light to future research avenues on VR enabled constructive visualization.